Problems and Perspective of Legal Education in China: A Qualitative Investigation - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
Legal education is a fundamental connection in the Chinese general set of laws, especially when China has vowed to administer the country by law and order. Legal education is a vital stage for individuals working within the legal profession, preparing judges, lawyers, and other legal staff. Lawful instruction within the setting of 21st Century China has two fundamental missions: first, working with the nation's science & schooling drive, and second, working with law and order in the country. Without the advancement of legal education, law and order may be something like an unfilled word. The mission of legal training has become more down-to-earth in serving the advancement of the market economy growth. The market-arranged financial advancement has achieved a deep level of interest in modern legal administrations. Legal education has grown broadly over the most recent twenty years. Lawful training and legal practice are still generally independent. A sample of 241 respondents was surveyed to determine the factors determining the Problems and Perspective of Legal Education in China. The study concludes that the Quality of legal education, Education and Demand, Reforms and Perspective, and Practical skill training are the factors that determine the Problems and Perspective of Legal Education in China.